(untitled) (Revista horizonte, 2011)
The influence of environmental stimulation and gross motor skills on the level of development of both variables in preschool children from two early childhood education centers, Junji, was analyzed. The methodology consists of a total sample of 24 children, aged 3 and 5 years, corresponding to a descriptive-correlational study. A semi-structured interview, HOME, was used to measure the environmental stimulation variable. For the measurement of gross motor skills, the motor battery, TGMD-2, was used. The main result was a low motor performance in children, expressed in 75% for locomotion skills and 70.5% for object control skills. Likewise, it was found that the level of environmental stimulation at home was low in 58.3% of the children and medium in 41.7% of them.